1998
DOI: 10.1021/es971033q
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between a Hydrophobic Organic Chemical and Natural Organic Matter:  Equilibrium and Kinetic Studies

Abstract: Interactions between a well-characterized, purified, peat humic acid and pentachlorobenzene were studied in equilibrium and kinetic experiments. The kinetic experiments, performed with a gas-purge method, showed the presence of a fast-desorbing, labile fraction and a slow-desorbing, nonlabile fraction. Increased contact time did not change the measured continuous desorption curves. A desorption experiment with interrupted flow and the measured isotherm suggested nonlinear sorption behavior. A first-order model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 22 publications
3
38
0
2
Order By: Relevance
“…3) because HSCAM has rigid structures, which should not be altered by cations. Furthermore, nonlinear isotherms of HOCs were reported for dissolved soil organic matter (Maxin and Kogel-Knabner 1995;Schlebaum et. al.…”
Section: Resultsmentioning
confidence: 99%
“…3) because HSCAM has rigid structures, which should not be altered by cations. Furthermore, nonlinear isotherms of HOCs were reported for dissolved soil organic matter (Maxin and Kogel-Knabner 1995;Schlebaum et. al.…”
Section: Resultsmentioning
confidence: 99%
“…In Schlebaum et al's study, results showed that part of pentachlorobenzene sorbed to a dissolved humic acid resisted desorption. And they proposed the likely mechanism that the non-labile fraction was a consequence of a change of conformation of the HA after the binding of pentachlorobenzene [17]. Ge et al observed a more compact conformation of humic substance assemblies after the sorption of naphthalene using atomic force microscopy [40].…”
Section: Possible Mechanisms Contributing To Desorption Resistancementioning
confidence: 99%
“…Weber et al introduced a composite model, the distributed reactivity model for sorption by soils and sediments to characterize intrinsic heterogeneities in the properties and behaviors of soils and sediments [16]. A similar model was applied by Schlebaum in a study with humic acid (HA) [17]. These models were parallel models with discrete sites that may have different affinities for HOCs and different sorption mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In Schlebaum et al's study, the results showed that part of pentachlorobenzene sorbed to a dissolved humic acid (HA) resisted desorption. They speculated that the nonlabile fraction was a consequence of a change of conformation of the HA after the binding of pentachlorobenzene [9]. Several different rate models have been used to describe desorption of HOCs from natural sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Time-integrated techniques have been used as infinite sink for desorbed compounds in the literature for time frames from a few hours to a few days. Examples of these methods include Tenaxaided desorption and equilibrium dialysis [5,9,[11][12][13]. Tenax extraction has advantages of high sorptive capacity and rapid adsorption from water.…”
Section: Introductionmentioning
confidence: 99%